Dampak Media Sosial Influencer Terhadap Minat Beli Konsumen dan Promosi Produk Sebagai Variabel Intervening - Ambo Sakka Hadmar (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to determine how much influence of beauty vlogger on consumer purchase intention through the promotion of perfume product. This research is a quantitative analysis with a sample of 100 respondents, who live in Jakarta and Bekasi and have used perfume products which are promoted by certain beauty vlogger (Rachel Goddard). The sample method is nonprobability sampling with purposive sampling techniques. The results of this study indicate that the direct effect is greater than the indirect effect because the influence of beauty vlogger is greater than promotion. The benefit of this research for Perfume Products is to increase consumer buying interest through promotion by beauty vlogger.